Karakterisasi Gugus Fungsi dan Sifat Fisik Komposit ZnO-PVA-Pati dari Kulit Pisang Goroho sebagai Bioplastik Antibakterial - Aisyah, Aisyah; Jahja, Mohamad; Mursalin, Mursalin; Irsan, Irsan; Ramadani, Andi Indra Wulan Sari (JFT : Jurnal Fisika dan Terapannya, 2024)
Plastic is one of the most widely used materials in everyday life to support various activities due to its versatile characteristics and functions. Bioplastic is one type of plastic that is easily decomposed naturally by microorganisms so that it becomes a more environmentally friendly compound. This study aims to analyze the characterization of functional groups and physical properties in goroho banana peel starch-based bioplastics with the addition of ZnO and PVA. The method used in this research is laboratory experimental method. The potential of goroho banana peel waste is abundant in Gorontalo Province and the starch content in goroho banana peel is 80.89%, so this research uses starch extracted from goroho banana peel with variations of ZnO addition (0.2%, 0.4%, 0.6%, 0.8%, 1%). The results showed that the addition of ZnO and PVA affected the functional groups and physical properties of bioplastics. The physical properties of bioplastics produced are in accordance with SNI standards, namely the amount of water uptake ranging from 1.39 to 8.21% and the length of bioplastics degraded on average less than 30 days.